1976
DOI: 10.1172/jci108310
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to glucagon in fetal hearts. Species variability and apparent disparities between changes in beating, adenylate cyclase activation, and cyclic AMP concentration.

Abstract: A B S T R A C T Previous studies of the ability of the immature heart to respond to glucagon have yielded conflicting results. To test the possibility that the apparent discrepancies might be explained in part by species variability, isolated hearts of fetal mice and rats (13-22 days' gestational age) were studied under identical conditions in vitro. Changes in atrial rate and ventricular contractility were measured in spontaneously beating hearts exposed to glucagon, and activation of adenylate cyclase was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A catecholamine-sensitive adenylate cyclase is present at this time (17) and as early as the thirteenth day in fetal rats ( 18). Clucagon responsiveness (chronotropic) of the fetal mouse heart is not observed until after the seventeenth day of fetal life, with the maximum response occurring somewhere between 19 and 22 (term) days ( 16). Theophylline, which inhibits phosphodiesterase, the enzyme catalyzing the breakdown of cyclic AMP to 5'-AMP has a significant chronotropic effect on the thirteenth to fourteenth day.…”
Section: Fig 2 Glucagon Activation Of Adenylate Cyclase In Fetal Amentioning
confidence: 99%
See 1 more Smart Citation
“…A catecholamine-sensitive adenylate cyclase is present at this time (17) and as early as the thirteenth day in fetal rats ( 18). Clucagon responsiveness (chronotropic) of the fetal mouse heart is not observed until after the seventeenth day of fetal life, with the maximum response occurring somewhere between 19 and 22 (term) days ( 16). Theophylline, which inhibits phosphodiesterase, the enzyme catalyzing the breakdown of cyclic AMP to 5'-AMP has a significant chronotropic effect on the thirteenth to fourteenth day.…”
Section: Fig 2 Glucagon Activation Of Adenylate Cyclase In Fetal Amentioning
confidence: 99%
“…Responsiveness to glucagon did not appear until after day 17 of fetal life. In another investigation he found that fetal rat hearts did not respond to glucagon until term (day 22) in marked contrast to what was observed with catecholamines ( 16). Clark, Beatty, and Allen showed that rat myocardial adenylate cyclase was not activated by glucagon ufitil approximately 28 days after birth (17).…”
mentioning
confidence: 98%
“…In the rat, the characteristic of indi vidual organs during days 21 -22 of gestation has been particularly well documented, with examination of the liver from day 16 of ges tation [Devos and Hers, 1974] and at 21 days of gestation [Watts and Gain, 1976]: kidney from 16 days before to 21 days after birth [Burch et al, 1971] and heart from 'less than 16 days of gestation" [Wildenthal et al, 1976] to 21 and 22 days of gestation [Wil denthal et al, 1976;Vinicor et al, 1974;Clark, 1973].…”
Section: Introductionmentioning
confidence: 99%
“…Each fetal mouse heart is cultured individually and is maintained at a gas-medium interface on a stainless steel grid (Wildenthal, 1971). Under control conditions (incubation with at least 30% oxygen and with standard culture medium [minimal essential medium (MEM) GIBCOJ), the hearts beat spontaneously and respond appropriately to pharmacological agents such as isoproterenol (Chen et al, 1979) or glucagon (Wildenthal et al, 1976). The principal characteristic of this preparation is that the myocardium is nourished by diffusion of nutrients from the culture medium, independent of coronary blood flow.…”
mentioning
confidence: 99%
“…By adding pharmacological agents to the culture medium, the effect of these agents on myocardial protection during simulated ischemia can be studied (Wildenthal et al, 1976). In this model, a protective effect has previously been demonstrated with insulin (Wildenthal et al, 1976), hypothermia (Roeske et al, 1977), graded increases in oxygen (Ingwall et al, 1979), and resupply of oxygen and oxidizable substrates after injury (Kloner and Ingwall, 1980).…”
mentioning
confidence: 99%